Customer loyalty toward internet banking in Nigeria - Ibrahim Aishatu Ogiri, 1978- author; Lim, Guan Choo, supervisor; Fakulti Pengurusan (2014)
Thesis (Sarjana Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2014